MAPPING INSOMNIA SEVERITY AMONG PROLANIS PATIENTS: A FORMATIVE STUDY IN A REMOTE AREA OF INDONESIA - Bachtiar, Vania Angeline; Sebong, Perigrinus Hermin; Pratiwi, Fransiska Inka; Sutanto, Eviana Budiarti; Mandagie, Aprilia Karen; Christyana, To Lidwina Prillya Indra; Santoso, Ferry (Jurnal Pranata Biomedika, 2026)
Background: poor sleep quality among type-2 diabetes mellitus and hypertension patients is a neglected issue in pursuing a continuum of care for the patients. Only little information is available concerning the association between hypertensive and diabetes mellitus conditions and poor quality of sleep among the Indonesian elderly in rural areas. This study aims to assess insomnia severity among PROLANIS patients.Methods: formative research was applied to map the current occurrence of insomnia severity among medical PROLANIS patients Puskesmas Pasir Sakti Lampung Timur. Data were collected through self-questionnaires (n=43). Univariate and ANOVA tests were used with significance (p-value 0.05). Results: the study included 43 participants, with a mean age of 66.02 (± 8.25). The Insomnia Severity Index mean scores were 12.26  ± 5.13 (hypertension), 8.67 ± 7.02 (type-2 diabetes mellitus), and 7.65 ± 5.84 (type-2 diabetes mellitus + hypertension). Our study showed significant differences in the insomnia severity index score between chronic conditions.Conclusions: There was a considerable difference in insomnia severity and sleep hygiene between patients with hypertension, type-2 diabetes mellitus, and type-2 diabetes mellitus + hypertension. Also, sleep hygiene significantly differed between routine and non-medical intake. Future assessment of sleep hygiene and insomnia severity should be intensive and incorporated into the PROLANIS program in Puskesmas. It is also needed for sleep quality literacy interventions among patients in rural areas.